2014
DOI: 10.1186/1471-2393-14-212
|View full text |Cite
|
Sign up to set email alerts
|

Maternal venous hemodynamics in gestational hypertension and preeclampsia

Abstract: BackgroundTo evaluate characteristics of venous hemodynamics, together with cardiac and arterial function, in uncomplicated pregnancies (UP), non-proteinuric gestational hypertension (GH) and preeclampsia (PE).MethodsIn this observational cross-sectional study, venous hemodynamics was assessed using a standardised protocol for combined electrocardiogram (ECG)-Doppler ultrasonography, together with a non-invasive standardised cardiovascular assessment using impedance cardiography (ICG) in 13 women with UP, 21 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 40 publications
2
36
1
3
Order By: Relevance
“…Contrary to observations in PE, in non‐proteinuric gestational hypertension, venous Doppler wave measurements do not differ from those in uncomplicated pregnancies. This suggests that venous hemodynamic dysfunction may be a pathophysiological feature of PE but not of gestational hypertension.…”
Section: Maladaptations Of Venous Hemodynamics and Plasma Volume In Pcontrasting
confidence: 69%
See 2 more Smart Citations
“…Contrary to observations in PE, in non‐proteinuric gestational hypertension, venous Doppler wave measurements do not differ from those in uncomplicated pregnancies. This suggests that venous hemodynamic dysfunction may be a pathophysiological feature of PE but not of gestational hypertension.…”
Section: Maladaptations Of Venous Hemodynamics and Plasma Volume In Pcontrasting
confidence: 69%
“…VPTT is shorter in PE than in normal pregnancy, and this is more pronounced in early‐ than in late‐onset PE. PE‐related shortening of VPTT occurs simultaneously at the arterial and venous sites, reflecting stiffening of the vascular wall, probably owing to increased vascular tone.…”
Section: Maladaptations Of Venous Hemodynamics and Plasma Volume In Pmentioning
confidence: 94%
See 1 more Smart Citation
“…There is sparse information about the venous circulation in preeclampsia, but Gyselaers et al [37] have reported venous haemodynamic dysfunction in preeclampsia, presenting weeks before clinical onset of disease.…”
Section: Severe Preeclampsiamentioning
confidence: 98%
“…More recently, ECG‐guided Doppler assessment of maternal venous haemodynamics in preeclampsia demonstrated that renal interlobar venous impedance index is increased several weeks before the onset of early preeclampsia, is raised much higher, has an parallel left‐right undulating pattern and is associated with a shorter venous pulse transit time compared to late preeclampsia (Gyselaers et al . , , ; Mesens et al . ).…”
Section: Cardiorenal Syndromesmentioning
confidence: 99%